2013
DOI: 10.3126/njst.v13i2.7728
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Discourse of Lakes in Nepal

Abstract: Over 5,000 standing water bodies, including those <1 ha and spread in 74 districts of Nepal have been scanned on the topographic sheets (scale of 1:125,000). Majority of these lakes or ponds are either in the high altitudes (above 3,000 m) or in lowland Tarai (below 500 m). In a literature review we found over 163 research studies conducted since the first study of lakes in 1969 in Khumbu region, majority being at the initiative of national academia, their faculties and graduate students. However, a complete i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…https://doi.org/10. 3126/njes.v8i1.34464 In Nepal, approximately 5,385 lakes have been recorded, of which 419 lakes are located in the mid-hills between 500 m to 2,999 m (Bhuju et al, 2013). Ramaroshan Lake Complex Area (RLCA) is an aesthetically, culturally and ecologically important area that is facing several threats mainly caused by anthropogenic activities such as unsustainable grazing, fishing, foraging, and fodder collection.…”
Section: Research Articlementioning
confidence: 99%
“…https://doi.org/10. 3126/njes.v8i1.34464 In Nepal, approximately 5,385 lakes have been recorded, of which 419 lakes are located in the mid-hills between 500 m to 2,999 m (Bhuju et al, 2013). Ramaroshan Lake Complex Area (RLCA) is an aesthetically, culturally and ecologically important area that is facing several threats mainly caused by anthropogenic activities such as unsustainable grazing, fishing, foraging, and fodder collection.…”
Section: Research Articlementioning
confidence: 99%
“…There are more than 5000 lakes in Nepal having an area of >1 ha and out of them, ten are listed in the list of Ramsar site [11]. The previous studies showed that the wetlands of Nepal are under threat by both natural and anthropogenic interferences and, hence the livelihoods of several wetland dependent communities are directly affected [4]. When sewage and agricultural run-off containing phosphates or other nutrients enter natural water bodies, they cause over nutrition, leading to eutrophication [7].…”
Section: Introductionmentioning
confidence: 99%
“…Fragility and sensitiveness are the main characteristics of HAWs and any small change in the water chemistry, either naturally or through anthropogenic disturbances, could lead to large impacts on their ecosystems, directly affecting the flora and fauna in them. Acid deposition during the spring season is a major threat to most of the HAWs in Nepal (Bhuju et al 2012); and the mercury and cadmium in the Gokyo wetlands is thought to result from long range transport by monsoon precipitation originating from industrial areas of lowland parts of the country, including that of India (Sharma et al 2012). Water pollution, mainly from hotels and lodges and religious rituals, also affects water chemistry.…”
Section: Threats Future Challenges and Remedial Measuresmentioning
confidence: 99%